Truciciele na dworze cesarskim! O przypadkach otruć za panowania dynastii julijsko-klaudyjskiej - Lampkowska, Paulina (Studia Europaea Gnesnensia, 2010)
The article examines the phenomenon of poisoning at the imperial court during the reign of Julio-Claudian dynasty, contrasted with the state of affairs in the Republican period. Drawing on the source texts and the latest scientific hypotheses, the author discusses consecutive cases of Drusus, Germanicus and Claudius on the one hand, and the murderous deeds of emperor Nero on the other. This paper attempts to reopen investigation and establish a diagnosis against the background of that period.